2017
DOI: 10.1088/1361-6382/aa691d
|View full text |Cite
|
Sign up to set email alerts
|

Analytical derivation of second-order deflection in the equatorial plane of a radially moving Kerr–Newman black hole

Abstract: In this work, we base on the second-order post-Minkowskian equations of motion, and apply an iterative technique to analytically derive the gravitational deflection of the relativistic particles in the equatorial plane of Kerr-Newman black hole with a radial (or longitudinal) and constant velocity. We find that the kinematically correctional effects on the second-order contributions to the deflection can be expressed into a very compact form, which are valid for both the massive particle and photon. Our result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Recently, He and Lin [10] considered the gravitational deflection of relativistic massive particles and light caused by a moving Kerr-Newman source numerically, and found that the second-order Schwarzschild contribution was in agreement with the former. This consistency was further confirmed by the analytical calculation via an iterative technique [11]. There were also other investigations devoted to the deflection of massive particles in static and spherically symmetric spacetimes [12][13][14], with their results matching with the Accioly and Ragusa's proposal.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Recently, He and Lin [10] considered the gravitational deflection of relativistic massive particles and light caused by a moving Kerr-Newman source numerically, and found that the second-order Schwarzschild contribution was in agreement with the former. This consistency was further confirmed by the analytical calculation via an iterative technique [11]. There were also other investigations devoted to the deflection of massive particles in static and spherically symmetric spacetimes [12][13][14], with their results matching with the Accioly and Ragusa's proposal.…”
Section: Introductionsupporting
confidence: 71%
“…Ref. [11]. Since different gauge leads to different coordinates for a given geometry, we actually verify further that the gravitational deflection angle of a test particle is independent on concrete coordinates, including the radiation-gauge coordinates [15,16].…”
Section: Ticles In Radiation Gaugesupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, we only provide some hints of its gravitational lensing signals. More sophisticated investigations with inclusion of its spin in the weak [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] and strong [114][115][116][117][118] deflection lensing as well as general relativistic magnetohydrodynamics of plasma are indeed needed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…with the affine parameter ξ B of the observer being given to be X B in the asymptotically flat spacetime [49,51]. It is worth to point out that there might be several numerical values of ξ A to correspond to a given X A in the strong field limit, and we take the one whose value is closest to X A in the following calculations for physical reasons.…”
Section: Basics Of Numerical Simulationsmentioning
confidence: 99%